2019
DOI: 10.18203/2320-1770.ijrcog20190265
|View full text |Cite
|
Sign up to set email alerts
|

Mullerian ductal anomalies and its outcome

Abstract: Background: The aim is to study various investigative modalities to diagnose Mullerian anomalies and to evaluate the reproductive outcome that occurs as a result of malformation of genital tract.Methods: A prospective study of reproductive anomalies and its outcome was performed by using data from women with congenital anomalies attended in OPD either with complains or for operative treatment or incidental diagnosis during caesarean section, manual removal of placenta, during laparoscopy or laparotomy at terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…[7] and Cahen-Peretz et al 2019. [8] and contrary to the findings published earlier by Vyas et al [9] who reported that the majority of CUAs related to gynecological cases were observed at 19.03 years. This discrepancy could be explained, according to the author's opinion, by the fact that some of the patients involved in our study might deny their pre-marriage complaints or knowledge about the presence of an anomaly and that they discovered this during the course of the management plane for infertility or obstetric complications.…”
Section: Discussioncontrasting
confidence: 78%
“…[7] and Cahen-Peretz et al 2019. [8] and contrary to the findings published earlier by Vyas et al [9] who reported that the majority of CUAs related to gynecological cases were observed at 19.03 years. This discrepancy could be explained, according to the author's opinion, by the fact that some of the patients involved in our study might deny their pre-marriage complaints or knowledge about the presence of an anomaly and that they discovered this during the course of the management plane for infertility or obstetric complications.…”
Section: Discussioncontrasting
confidence: 78%
“…Similarly miscarriages were the common complication in a study conducted by Chan et al A meta-analysis have documented that there was increased relative risk by 2.89 time of first trimester abortions in mullerian anomalies, which is in line with our study findings. The current study reported a very high rate of caesarean section rate of 72.6% and is comparable to study by Raj et al where the caesarean rate was 63.3% as compared to 34.7% in Hua et al This high rate could be due to the reason that most of the anomalies are diagnosed incidentally during the pregnancy in most of the patients 10.…”
supporting
confidence: 86%
“…The mean age of the participants was 27.2 (5.1) years which is in line with the results of a study conducted by Vyas et al in which the maternal age was more in the age group of 21-25 years. 18 Various other studies across the globe also have reported similar results. 19,20 It could be due to the fact that the desire for pregnancy is higher during this age group and hence the attitude for seeking care for uterine anomalies.…”
Section: Discussionsupporting
confidence: 60%
“…A study conducted by Hua et al and Vyas et al have shown that cephalic presentation was common and breech accounted for only around 1/4 th of the participants. 18,21 Bicornuate uterus was the most common uterine anomaly (45.2%) followed by arcuateuterus (19.3%) while septate uterus was present in 14.5% of the pregnant women. Surprisingly, these results are in contrast to the available literature where septate uterus followed by bicornuate uterus was believed to be the common uterine anomaly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation